The Determinant Of Entrepreneurial Orientation Of Household Industries Of Local Food In Bogor Regency, West Java - Faizal Maad; Tun Susdiyanti; Linar Humaira; Anak Agung Eka Suwarnata; Yunus Arifien (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The study aimed (1) to analyze the level of entrepreneurial orientation of local food home industry entrepreneurs and (2) to analyze the determinant factors of the entrepreneurial orientation of local food industry entrepreneurs in Bogor Regency. This research was carried out in 14 sub-districts and 20 villages in the center of local food production in Bogor districts involving 214 local food industry household entrepreneurs. Data analysis was simulated using structural equation models (SEM). The results of this study indicate that the entrepreneurial orientation of local food home industry entrepreneurs in Bogor Regency is classified as weak. The determinant factor of the entrepreneurial orientation of local food home industry entrepreneurs consists of individual characteristics of local food industry entrepreneurs; support of government policies on the development of the local food house industry; and entrepreneurial competence. To strengthen the entrepreneurial orientation of local food home industry entrepreneurs, it is necessary to improve the characteristics of entrepreneurship, especially the increase in non-formal education, entrepreneurial entrepreneurship; the remembrance of government policy support in the development of local food home industry and entrepreneurial entrepreneurship of local food industry entrepreneurs